2019
DOI: 10.1038/s41598-018-35670-3
|View full text |Cite|
|
Sign up to set email alerts
|

Seagrass can mitigate negative ocean acidification effects on calcifying algae

Abstract: The ultimate effect that ocean acidification (OA) and warming will have on the physiology of calcifying algae is still largely uncertain. Responses depend on the complex interactions between seawater chemistry, global/local stressors and species-specific physiologies. There is a significant gap regarding the effect that metabolic interactions between coexisting species may have on local seawater chemistry and the concurrent effect of OA. Here, we manipulated CO2 and temperature to evaluate the physiological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…Our study highlights that biologically active surfaces further add complexity to conditions experienced within the DBL that may not be beneficial for calcifiers tested herein. Thus, future studies should consider the following aspects; (1) the possibility that chemical defenses or other surface characteristics might overwrite the mitigation potential offered by macrophytes under OA scenarios, as shown for the BBL in some studies (Wahl et al 2018; Bergstrom et al 2019), and (2) determining how energy resources are exploited when organisms are exposed to different OA conditions (stable or fluctuating). It is imperative that studies explore the concept of refugia and how this is defined (Kapsenberg and Cyronak 2019), but also characterize their biological benefits and drawbacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study highlights that biologically active surfaces further add complexity to conditions experienced within the DBL that may not be beneficial for calcifiers tested herein. Thus, future studies should consider the following aspects; (1) the possibility that chemical defenses or other surface characteristics might overwrite the mitigation potential offered by macrophytes under OA scenarios, as shown for the BBL in some studies (Wahl et al 2018; Bergstrom et al 2019), and (2) determining how energy resources are exploited when organisms are exposed to different OA conditions (stable or fluctuating). It is imperative that studies explore the concept of refugia and how this is defined (Kapsenberg and Cyronak 2019), but also characterize their biological benefits and drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Under OA the higher availability of CO 2 could enhance macrophyte photosynthesis (Saderne 2012; Cornwall et al 2017), although such beneficial effects were not observed for all macrophytes (Britton et al 2016; Cornwall et al 2017). Yet a “boost” of photosynthesis by OA further increase pH fluctuations in macrophyte boundary layers and could provide increased temporal refugia from acidification stress during daytime for organisms that live inside these boundary layers (Teagle et al 2017; Bergstrom et al 2019). The magnitude of pH fluctuations and hence the OA buffering capacity of macrophytes, however, also depends on the structural composition of macrophyte communities and the hydrodynamic conditions that prevail (Hurd 2000; Wahl et al 2015).…”
Section: Figmentioning
confidence: 99%
“…These alterations in availability and energy flows must be considered in conservation and management strategies to minimize risks, including a discussion about the ecosystem's socio-environmental and ethical aspects (VÉRGES et al, 2019). When the distribution of key ecosystems for coastal resilience is mapped, they are seen as irreplaceable due to their role for biodiversity (COPERTINO et al, 2017), climate (BERGSTROM et al, 2019) and fishing stocks regulators (WEATHERDON et al, 2016), albeit under threat of multiple stressors in the Brazilian EEZ (MAGRIS et al, 2020) (Figure 4). unep-wcmc.org;Giri et al (2011), Carvalho et al (2020 and Horta et al (2016).…”
Section: Potential Distribution Modellingmentioning
confidence: 99%
“…This role as carbon sink helps mitigate the damage caused by sea acidification to reef ecosystems and calcifying species. The daily CO 2 absorption by these primary producers may represent a solution and local adaptation for activities such as shellfish aquaculture, or in situ conservation of calcifying organisms, as these primary producers may mitigate acidification effects (BERGSTROM et al, 2019).…”
Section: Potential Distribution Modellingmentioning
confidence: 99%
See 1 more Smart Citation